2020
DOI: 10.1002/cam4.2860
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Long non‐coding RNA ARAP1‐AS1 promotes tumorigenesis and metastasis through facilitating proto‐oncogene c‐Myc translation via dissociating PSF/PTB dimer in cervical cancer

Abstract: Long non‐coding RNA (lncRNA) is emerging as a pivotal regulator in tumorigenesis and aggressive progression. Here, we focused on an oncogenic lncRNA, ARAP1 antisense RNA 1 (ARAP1‐AS1), which was notably upregulated in cervical cancer (CC) tissues, cell lines and serum. High ARAP1‐AS1 expression was closely associated with larger tumor size, advanced FIGO stage as well as lymph node metastasis. Importantly, it was identified as an effective diagnostic and prognostic biomarker for CC. In vitro and in vivo assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…The hnRNP I knockdown reduces the proliferation and anchorage-independent growth while increasing invasiveness of HeLa cells . The hnRNP I was also shown to regulate gene expression by forming a dimer with PTB-associated splicing factor (PSF) in SiHa and CaSki cells (Zhang et al, 2020). Moreover, Zhang et al (2020) demonstrated that lncRNA ARAP1-AS1 interacts with PSF causing the release of hnRNP I, which in turns enhances the c-Myc IRES-dependent translation by binding to c-Myc mRNA 5 -UTR enhancing SiHa and Caski cell proliferation.…”
Section: Splicing Factors Deregulation In Cervical Cancermentioning
confidence: 99%
“…The hnRNP I knockdown reduces the proliferation and anchorage-independent growth while increasing invasiveness of HeLa cells . The hnRNP I was also shown to regulate gene expression by forming a dimer with PTB-associated splicing factor (PSF) in SiHa and CaSki cells (Zhang et al, 2020). Moreover, Zhang et al (2020) demonstrated that lncRNA ARAP1-AS1 interacts with PSF causing the release of hnRNP I, which in turns enhances the c-Myc IRES-dependent translation by binding to c-Myc mRNA 5 -UTR enhancing SiHa and Caski cell proliferation.…”
Section: Splicing Factors Deregulation In Cervical Cancermentioning
confidence: 99%
“…Zhang et al reported that the lncRNA ARAP1-AS1 drives the translation of proto-oncogene c-myc by directly interacting with PSF protein and further affect the internal ribosome entry site (IRES) function. Up-regulation of c-myc driven by ARAP1-AS1 facilitates the development and progression of cervical cancer [16]. Another lncRNA GMAN is shown to directly interact with EIF4b and promote its phosphorylation and stability [17].…”
Section: Discussionmentioning
confidence: 99%
“…As is known, lncRNA does not possess the ability to transcribe and translate into functional proteins in cells, but it can regulate gene expression in a variety of ways (24). In recent years, lncRNA ARAP1-AS1 has been newly identified as a regulatory molecule, and is currently found to be highly expressed in colon, gastric, and cervical cancers, as well as being involved in the occurrence and development of tumors (18,20,25). LncRNA ARAP1-AS1 is highly expressed in colorectal cancer tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…SYBR Green dye method was used for the RT-PCR reaction. The ΔΔCt method was used to calculate the relative expression of lncRNA ARAP1-AS1; glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as an internal reference gene, and the lncRNA ARAP1-AS1 and GAPDH primer sequences were used as references (20).…”
Section: Rt-pcr Methods To Detect the Expression Of Lncrna Arap1-as1mentioning
confidence: 99%